2002
DOI: 10.1016/s0014-5793(02)02914-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of cell lines derived from T‐cell malignancies

Abstract: The expression pro¢les of eight cell lines derived from T-cell malignancies were compared to CD4-positive T-cells using cDNA microarray technology. Unsupervised hierarchical clustering of 4364 genes demonstrated substantial heterogeneity resulting in four distinct groups. While no genes were found to be uniformly up-or down-regulated across all cell lines, we observed 111 over-expressed genes (greater than two-fold) and 1118 down-regulated genes (greater than two-fold) in the lymphomas as a group when compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…We maintain that much fewer genes, compared with those that differentiate peripheral T-cell lymphoma and lymphoblastic T-cell lymphomas, might be distinguishing among the different subtypes of periph- eral T-cell lymphoma. Using different T-cell lines, significant heterogeneity in the expression profiles has been previously reported, although not with a complete correlation to the clinicopathologically related categories (14). In contrast, the comparison of peripheral T-cell lymphoma with normal samples revealed a subset of 17 and 35 significantly differentially expressed genes between all peripheral T-cell lymphoma tumors and normal T lymphocytes or reactive lymph nodes, respectively (see Fig.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…We maintain that much fewer genes, compared with those that differentiate peripheral T-cell lymphoma and lymphoblastic T-cell lymphomas, might be distinguishing among the different subtypes of periph- eral T-cell lymphoma. Using different T-cell lines, significant heterogeneity in the expression profiles has been previously reported, although not with a complete correlation to the clinicopathologically related categories (14). In contrast, the comparison of peripheral T-cell lymphoma with normal samples revealed a subset of 17 and 35 significantly differentially expressed genes between all peripheral T-cell lymphoma tumors and normal T lymphocytes or reactive lymph nodes, respectively (see Fig.…”
Section: Discussionmentioning
confidence: 91%
“…A supervised method was then used to find the more significant (adjusted P Ͻ 0.05) differentially expressed genes among peripheral T-cell lymphomas and lymphoblastic T-cell lymphomas (see supplementary data online). 14 We found 184 clones representing 160 genes that were differentially expressed between these two classes (Fig. 2).…”
Section: Gene Expression Profiles Of Primary T-cell Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…32-35 T-cell lymphomas represent a heterogeneous group of tumors that could benefit from DNA microarrays for defining unrecognized subcategories, identifying new oncogenic pathways or pathogenetically relevant genes and biologic predictors for their clinical course. With the exception of previous reports based on cell lines derived from T-cell malignancies, [36][37][38] few studies involve biopsy specimens from patients with T-cell lymphomas. [32][33][34][35] In the study by Martinez-Delgado et al, 32 gene-expression profiles have been analyzed in 34 peripheral T-cell lymphoma pertaining to different categories.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of several B-NHLs series has led to the definition of molecular subgroups with specific outcomes (Alizadeh et al, 2000;Rosenwald et al, 2002;Shipp et al, 2002;Thieblemont et al, 2004). In contrast, only a limited number of T-cell neoplasms have been investigated using microarrays, including mycosis fungoides (Tracey et al, 2003), leukemic phase of cutaneous T-NHL (Kari et al, 2003), cell lines derived from T-cell malignancies (Li et al, 2001;Fillmore et al, 2002), or PTCL (Martinez-Delgado et al, 2004). A recent profiling analysis was focused on the comparison between PTCL and T-lymphoblastic lymphoma (T-LBL) types (Martinez-Delgado et al, 2004), but a molecular classification of PTCL entities has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%